PARTICULARIDADES DO USO CLÍNICO DO PROPOFOL EM FELINOS DOMÉSTICOS - Silva, Letícia Gonçalves da; Fernandes, Amanda Ladeia; Lubiana, Isaac Scherre; Lima, Marcos Paulo Antunes de (Sinapse Múltipla, 2020)